Management of Gingival Enlargement in Patient with Fixed Orthodontic Appliances in Undiagnosed Type-2 Diabetic Patient: A Case Report - Evelyn Christina Muliyanto; R. A. Eka Yunanthi; Jovan Amadeo Muliyanto (GoAcademica Research & Publishing, 2025)
Gingival enlargement (GE) is a common periodontal condition that may result from inflammatory processes, medications, hormonal changes, or systemic diseases, including diabetes mellitus, which has a well-established bidirectional relationship with periodontal health. This case report aims to describe the clinical effectiveness of conventional gingivectomy in the management of gingival enlargement in an orthodontic patient with previously undiagnosed type 2 diabetes mellitus. A 37-year-old female undergoing fixed orthodontic treatment for two years presented with a complaint of gingival swelling in the mandibular anterior region accompanied by frequent bleeding during tooth brushing for approximately one year. The patient denied persistent pain, prolonged bleeding, or any known systemic disease. Clinical examination revealed localized gingival enlargement, most prominent around tooth 33, with the presence of plaque and calculus accumulation. The enlarged gingival tissue covered nearly half of the clinical crown, corresponding to a gingival overgrowth index score of 2, contributing to plaque retention and aesthetic concerns. Further assessment revealed a random blood glucose level of 272 mg/dL, indicating uncontrolled type 2 diabetes mellitus, while blood pressure was within normal limits. Following medical management and stabilization of blood glucose levels, conventional scalpel gingivectomy and gingivoplasty were performed to remove excess gingival tissue, restore normal gingival contours, reduce plaque-retentive areas, support ongoing orthodontic treatment, and improve aesthetics. Postoperative evaluation demonstrated satisfactory healing and improvement in gingival morphology and oral hygiene maintenance. This case highlights that conventional gingivectomy is an effective treatment modality for gingival enlargement when appropriately indicated and underscores the importance of identifying and controlling underlying systemic conditions, particularly diabetes mellitus, to achieve favorable periodontal and surgical outcomes.